Neurovascular Coupling in Development and Disease: Focus on Astrocytes - Stackhouse, Teresa L.; Mishra, Anusha (Frontiers in Cell and Developmental Biology, 2021)
Neurovascular coupling is a crucial mechanism that matches the high energy demand of the brain with a supply of energy substrates from the blood. Signaling within the neurovascular unit is responsible for activity-dependent changes in cerebral blood flow. The strength and reliability of neurovascular coupling form the basis of non-invasive human neuroimaging techniques, including blood oxygen level dependent (BOLD) functional magnetic resonance imaging. Interestingly, BOLD signals are negative in infants, indicating a mismatch between metabolism and blood flow upon neural activation; this response is the opposite of that observed in healthy adults where activity evokes a large oversupply of blood flow. Negative neurovascular coupling has also been observed in rodents at early postnatal stages, further implying that this is a process that matures during development. This rationale is consistent with the morphological maturation of the neurovascular unit, which occurs over a similar time frame. While neurons differentiate before birth, astrocytes differentiate postnatally in rodents and the maturation of their complex morphology during the first few weeks of life links them with synapses and the vasculature. The vascular network is also incomplete in neonates and matures in parallel with astrocytes. Here, we review the timeline of the structural maturation of the neurovascular unit with special emphasis on astrocytes and the vascular tree and what it implies for functional maturation of neurovascular coupling. We also discuss similarities between immature astrocytes during development and reactive astrocytes in disease which are relevant to neurovascular coupling. Finally, we close by pointing out current gaps in knowledge that must be addressed to fully elucidate the mechanisms underlying neurovascular coupling maturation, with the expectation that this may also clarify astrocyte-dependent mechanisms of cerebrovascular impairment in neurodegenerative conditions in which reduced or negative neurovascular coupling is noted, such as stroke and Alzheimer’s disease.